Synthesis, characterization and revealing the sono-photochemical potential of new NIR BODIPY derivative - Karanlik, Gurkan (PERGAMON-ELSEVIER SCIENCE LTD, 2024)
Although the idea of combining the light of photodynamic therapy (PDT) and the sound of sonodynamic therapy (SDT) and converting into a much more effective therapeutic treatment method, sonophotodynamic therapy (SPDT), is very wise and sensitizing agents such as phthalocyanines produce higher amounts of singlet oxygen (1O2) 1 O 2 ) with this method, the usage of SPDT for boron-dipyrromethene (BODIPY)-based BODIPY )-based theranostics has put forward by our group for the first time and no studies have been published by other groups in the literature so far. Therefore, as our continuing motivation in this direction, in the present study, a novel near-infrared (NIR) NIR ) BODIPY fluorophore bearing thienyl-pyridine substituent at meso-position, iodines as heavy atoms at 2-,6- positions and distyryl segments at 3-,5- positions which enlarge It-conjugation of the molecule has been synthesized successfully. The structural characterizations of the target NIR BODIPY 2 has been accomplished by the conventional spectroscopic methods (1H 1 H NMR, 13 C NMR, FT-IR (ATR), UV-Vis and HRMS/MS) and elemental analysis. In order to evaluate the singlet oxygen generation capacity of NIR BODIPY 2 , photochemical and sonophotochemical methods have been employed comparatively. The singlet oxygen quantum yield (Phi Delta) Phi Delta ) of NIR BODIPY 2 was calculated 0.37 using by photochemical method, this value increased to 0.66 by sonophotochemical study. It can be said that these results will open new horizons for researchers in terms of understanding sonophotochemical measurements of BODIPY derivatives for future in vitro or in vivo studies.
Keywords: Sonophotodynamic therapy; Photodynamic therapy; Boron-dipyrromethene; Singlet oxygen; SONODYNAMIC THERAPY; DYES; DISCOVERY; Chemistry